Comparison of Stage 4 and Stage 4s Neuroblastoma Identifies Autophagy-Related Gene and LncRNA Signatures Associated With Prognosis - Meng, Xinyao; Li, Honglin; Fang, Erhu; Feng, Jiexiong; Zhao, Xiang (Frontiers in Oncology, 2020)
Background: The spontaneous regression of neuroublastoma (NB) is most prevalent and well documented in stage 4s NB patients. However, whether autophagy plays roles in the spontaneous regression of NB is unknown. Objective: To identify autophagy-related genes (ARGs) and autophagy-related long non-coding RNAs (lncRNAs) that differentially expressed in stage 4 and stage 4s NB, and to build prognostic risk signatures based on the ARGs and autophagy-related lncRNAs. Methods: One RNA-Seq dataset (TARGET NBL, n =153) was utilized as discovery cohort and two microarray datasets (n = 498 and n = 223) were used as validation cohorts. Differentially expressed ARGs were identified by comparing stage 4s and stage 4 NB samples. An ARG signature risk score and an autophagy-related lncRNA signature risk score were constructed. The receiver operating characteristic (ROC) curve analyses were used to evaluate the survival prediction ability of the two signatures. Gene function annotation and Gene Set Enrichment Analysis (GSEA) were performed to clarify the autophagic biological processes enriched in different risk groups. Results: Nine ARGs were integrated into the ARG signature. Patients in the high-risk group of the ARG signature had significantly poorer overall survival (OS) than patients in the low-risk group. The ROC curves analyses revealed that the ARG signature performed very well in predicting OS (5 years AUC = 0.81). Seven autophagy-related lncRNAs were integrated into the autophagy-related lncRNA signature. Patients in the high-risk group of the lncRNA signature had significantly poorer OS than patients in the low-risk group. The ROC curves analyses also revealed that the lncRNA signature performed well in predicting OS (5 years AUC = 0.77). Both of the ARG signature and lncRNA signature are independent with other clinical risk factors in the multivariate Cox regression survival analyses. GSEA analyses revealed that autophagy-related biological processes are enriched in low-risk groups. Conclusions: Autophagy-related genes and lncRNAs are differentially expressed between stage 4 and stage 4s NB. The ARG signature and autophagy-related lncRNA signature successfully stratified NB patients into two risk groups. Autophagy-related biological processes are highly enriched in low-risk NB groups.